2006
DOI: 10.1080/13638490500079476
|View full text |Cite
|
Sign up to set email alerts
|

Costs and complications of hospitalizations for children with cerebral palsy

Abstract: Hospitalization of children with CP represents a major expenditure for health care systems. Studies to improve the management of conditions associated with CP could result in better outcomes for children and families and potentially decrease costs associated with hospitalization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
65
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(67 citation statements)
references
References 16 publications
2
65
0
Order By: Relevance
“…They have a disproportionately high use of emergency care health services, and they experience frequent hospitalizations, with subsequently high readmission rates [12],[13]. When hospitalized, they tend to stay longer and have more expensive admissions than other children [14]. It is estimated that a large proportion of lifetime health-related costs for a children with severe NI is attributable to inpatient care [15].…”
Section: Introductionmentioning
confidence: 99%
“…They have a disproportionately high use of emergency care health services, and they experience frequent hospitalizations, with subsequently high readmission rates [12],[13]. When hospitalized, they tend to stay longer and have more expensive admissions than other children [14]. It is estimated that a large proportion of lifetime health-related costs for a children with severe NI is attributable to inpatient care [15].…”
Section: Introductionmentioning
confidence: 99%
“…This difference may be attributed to a difference in hospital care between adults and children, and the costs of inpatient stay may be higher when patients had surgery compared to a hospitalization without surgery. However, Murphy et al 22 showed average costs of US$ 15 478 (EURO 2014: €15 606, converted with PPP 11 ) per hospitalization related to musculoskeletal and connective tissue system disorders in the US (resource use collection was done in 1997), which is more than twice calculated hospital costs in this article. This may be due to the inclusion of more costly operations, e.g., operations on the lower extremities, spine, and hip.…”
Section: Resultsmentioning
confidence: 90%
“…[8][9][10]22 To gain more insight into the total health care costs of children with CP, further research is needed on costs of other treatments for children with, also other types of, CP. Furthermore, it is desired to weight costs against clinical parameters, providing hospital managers, insurance companies, and policy makers with valuable information on the relative efficiency of alternative options.…”
Section: Resultsmentioning
confidence: 99%
“…A Medline search of articles from the United States did not find such aggregate data specific to our country. Fortunately, the Kids Inpatient Database, KID 2003, developed by the Agency for Health care Research and Quality [1] provides an optimal source for such data that enables the ability to study rare, infrequent disease processes on a macro scale [2][3][4][5][6][7][8]. This database is ideally suited to study the incidence and resource use associated with retained foreign bodies during surgery.…”
mentioning
confidence: 99%